(untitled) (Eureka Journal of Computing Science & Digital Innovation, 2026)
The IT industry is currently utilizing technology of cloud computing. Cloud-based systems, reliant via the internet, possesses the utmost robust computational architectural design. It consists of a cohesive and interconnected array of technology, applications, and the network supporting the Internet. It possesses multiple roles at the upper section pertaining to the grid and within various computer systems. In this work, I reviewed over 30 cloud computing articles and gave a brief overview of the topic. The review’s findings illustrate the state pertaining to the information technology sector both prior to and subsequent to the cloud.